The impact of a Solar Market Garden programme on dietary diversity, women's nutritional status and micronutrient levels in Kalalé district of northern Benin. Issue 14 (8th July 2019) - Alaofè, Halimatou; Burney, Jennifer; Naylor, Rosamond; Taren, Douglas
Abstract: Objective: To examine the impacts of a Solar Market Garden 1-year solar-powered drip irrigation (SMG) programme in Kalalé district of northern Benin on mothers' nutritional status and micronutrient levels. Design: Using a quasi-experimental design, sixteen villages were assigned to four groups: (i) SMG women's groups (WG); (ii) comparison WG; (iii) SMG non-WG (NWG); and (iv) comparison NWG. Difference-in-differences (DID) estimates were used to assess impacts on mothers' food consumption, diversity, BMI, prevalence of underweight (BMI < 18·5 kg/m 2 ) and anaemia, and deficiencies of iron (ID) and vitamin A (VAD). Setting: Kalalé district, northern Benin. Participants: Non-pregnant mothers aged 15–49 years ( n 1737). Results: The SMG programme significantly increased mothers' intake of vegetables (DID = 25·31 percentage points (pp); P < 0·01), dietary diversity (DID = 0·74; P < 0·01) and marginally increased their intake of flesh foods (DID = 10·14 pp; P < 0·1). Mean BMI was significantly increased among SMG WG compared with the other three groups (DID = 0·44 kg/m 2 ; P < 0·05). The SMG programme also significantly decreased the prevalence of anaemia (DID = 12·86 pp; P < 0·01) but no impacts were found for the prevalence of underweight, ID and VAD. Conclusions: Improving mothers' dietary intake and anaemia prevalence supports the need to integrate gender-based agriculture to improve nutritional status. However, it may take more than a year, and additional nutrition and health programmes, to impact the prevalence of maternal underweight, ID and VAD.